STRATEGI INTEGRASI PEMBELAJARAN KONTEKSTUAL DAN NILAI KARAKTER PADA KURIKULUM PENDIDIKAN ISLAM - Nurrosyidah Rahmawati, Nanda; Katni Katni; Riyanto; Lia Rokhmawati (LPPM STAI Muhammadiyah Probolinggo, 2024)
This paper examines the strategic value of integrase models of contextual learning and character education for Islamic education. The contextual learning model is the right model and can be integrated for character education. The contextual learning model can enrich students' scientific repertoire and deduce knowledge deductively towards inductive knowledge. This model can produce meaningful learning and joyful learning in Islamic education. supporting factors and constraints in integrating contextual learning models and character education in Islamic educational institutions from intrinsic and extrinsic factors of students.